'Coursing the Tinkerley Fox': Tactics of Garrison Warfare in the West Midlands during 1643 and 1644. (2nd January 2022) - Worton, Jonathan
ABSTRACT: A military defeat for the parliamentarians in south Staffordshire in March 1644 involved the capitulation of their outpost at Stourton Castle to Worcestershire royalists. The beaten parliamentary commander was Colonel John Fox, who in autumn 1643 had established a garrison near Birmingham at Edgbaston. This, like Stourton Castle in turn, was one of the number of strongholds in the West Midlands the opposing sides held as a strategy for territorial control. Indeed, much of the fighting of the English Civil War of 1642–6 involved clashes between local garrison-based forces, sometimes fought for the possession of rival strongpoints. In March 1644 Fox enabled the parliamentarian seizure of Stourton Castle for reasons that also impelled inter-garrison warfare elsewhere. The subsequent short campaign to besiege or relieve the castle is reconstructed here, as a case study of the tactics and conduct of the localized military action that shaped the course of the wider war.